High intensity human activity limits ultra-high altitude soil microbial community dispersal and keystone taxa distribution in southeastern Tibetan Plateau - Liu, Wenzu; Ma, Hongfang; Dong, Mengyao; Song, Yaning; Wang, Ruihong; Hou, Zhuonan; Luo, Daqing; Ma, Heping; Wei, Yuquan (Frontiers in Microbiology, 2025)
Increasing human activities have caused ecological damage to the environment, especially in the ecologically sensitive alpine regions such as the southeastern Tibetan Plateau. However, how different intensities of human activities in the alpine regions affect the community assembly process of soil microorganisms and the distribution of keystone taxa remains unclear. This study examines the relationship between human activity intensity and soil microbial dynamics in three different Human Footprint Index (HFI) regions. The microbial community structure and assembly processes were investigated within over 200 km from Gongbo’gyamda County to Bayi District in the southeastern section of Tibet. The results show that human activities changed the content of soil nitrogen (r = 0.50) and phosphorus (r = −0.46), which affected bacterial diversity (phosphorus for Sobs, r = −0.41, for Shannon index, r = −0.37; nitrogen for Shannon index, r = 0.37). Human activities increase the complexity of microbial networks but decrease the stability of soil micro-ecosystems. As elevtation increases, the dispersal limitation of microbial communities decreases (total effect size: bacterial = −0.705, fungal = −0.745). However, human activities directly or indirectly exacerbate this diffusion limitation (total effect size: bacterial = 0.488, fungal = 0.252). Keystone taxa are closely related to the assembly processes, which could significantly restrain the dispersal limiation of microbial community, especially fungal (r = −0.458). These insights help to understand the ecological impact of human disturbances on microbial networks and provide a basis for future conservation strategies aimed at mitigating biodiversity loss in fragile ecosystems like southeastern Tibet.